Dogs Have Their Day - New Straits Times, Shella Sri Priya (2008)
More than 600 dogs of different breed were unleashed to make their way into the Malaysian Books of Records in a dogathon organised by Universiti Putra Malaysia's Faculty of veterinary Medicine's Zoologico.